The Success of Young Entrepreneurs in Bengkulu City: An Analysis of Micro and Macro Factors - Septa Adiguna Putra; Ahmad Soleh; Rina Trisna Yanti (Universitas Dehasen Bengkulu, 2026)
This study aims to determine the influence of micro and macro factors on the success of young entrepreneurs in Bengkulu City. This research is quantitative in nature, with a sample of 30 young entrepreneurs in Bengkulu City. Data were collected using questionnaires, and the analytical methods used were multiple linear regression, partial tests, and hypothesis testing. The results of the study show that the micro factor variable has a significance value of 0.001 < 0.05 or a t-count value greater than the t-table value (4.292 > 2.051). This means that the first hypothesis (H1) is accepted because partially the micro factor (X1) has a significant effect on the success of young entrepreneurs in Bengkulu City (Y). The macro factor variable (X2) has a significance value of 0.001 < 0.05 or a t-count value greater than the t-table value (3.817 > 2.051). This means that the second hypothesis (H2) is accepted because partially the macro factor (X2) has a significant effect on the success of young entrepreneurs in Bengkulu City (Y). Based on the results of simultaneous hypothesis testing. With an F-value of 165.103 >3.354, it indicates that simultaneously the micro factor variable (X1) and the macro factor variable (X2) have a positive and significant effect on the success of young entrepreneurs in Bengkulu City (Y).